2021
DOI: 10.1039/d0cp05665k
|View full text |Cite
|
Sign up to set email alerts
|

A Ni-doping-induced phase transition and electron evolution in cobalt hexacyanoferrate as a stable cathode for sodium-ion batteries

Abstract: The charge density differences in different charge states reflect the contributions of each transition-metal atom to the electron transfer process, fundamentally revealing the formation mechanism of the three pairs of redox peaks shown by NCHCF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Among them, metal-ion doping is currently one of the most effective modification methods. The metal ions are usually doped at the M-site or Na-site. K + are usually doped at the Na-site, while transition-metal ions such as Co 2+ , Ni 2+ , and Mn 2+ are usually doped at the M-site. In contrast, there are more studies on doping at the M-site. Since You et al , found the “zero-strain” characteristics of NiHCF during the desodiation/sodiation process, Ni is often used as a doping element to improve the cycle stability of MHCF.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, metal-ion doping is currently one of the most effective modification methods. The metal ions are usually doped at the M-site or Na-site. K + are usually doped at the Na-site, while transition-metal ions such as Co 2+ , Ni 2+ , and Mn 2+ are usually doped at the M-site. In contrast, there are more studies on doping at the M-site. Since You et al , found the “zero-strain” characteristics of NiHCF during the desodiation/sodiation process, Ni is often used as a doping element to improve the cycle stability of MHCF.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, the low‐voltage plateau corresponding to a redox reaction on FeN 6 center and the high‐voltage plateau corresponding to a redox reaction on FeC 6 octahedra that occurred during the cycling of FeHCF@VCSC also undergo reversible evolution in XPS spectra, accompanied by the changes of peak shift and peak area of Fe 2p, reflecting the reversible Na‐ions insertion/extraction processes. [ 20,37 ]…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, the applications on PBAs of ex situ XPS are mainly for the analysis of pristine powder and disassembled electrode sheets after cycles for PBAs. Jiang et al [131] studied the evolution of the electronic state information under different charge/discharge states via ex situ XPS. As shown in Figure 9B, the Fe peaks retain consistent shapes but are shifted to higher binding energies.…”
Section: (14 Of 19)mentioning
confidence: 99%
“…Reproduced with permission. [ 131 ] Copyright 2021, The Royal Society of Chemistry. C) Mössbauer spectra of PB‐1, PB‐3, and PB‐5 samples.…”
Section: Advanced Techniques For Pbas Cathodesmentioning
confidence: 99%
See 1 more Smart Citation